The use of vibrational spectroscopy in the geographic characterization of human teeth: a systematic review. Issue 2 (7th February 2020) - Pretorius, Nellie Elizabeth; Power, A.; Tennant, M.; Forrest, A.; Cozzolino, Daniel
Abstract: The paper reviews the applications of vibrational spectroscopy for the analysis of teeth. A systematic search of literature published between 1990 and 2018 in the following databases: PubMed/MEDLINE, the Cochrane Library, Academic Search Ultimate, and Google Scholar was completed. Peer reviewed original papers and reviews were searched using the following keywords and phrases in different combinations: teeth/tooth, dental, vibrational spectroscopy, near-infrared spectroscopy (NIR), Raman spectroscopy, Fourier-transform infrared spectroscopy (FTIR), mineralized tissue, hydroxyapatite, geographic, profiling, and characterization. A total of 173 articles matched the inclusion criteria. Of these, 35 studies discussed dental decay; 11 outlined dental maturation and developmental dental defects; 30 assessed demineralization, remineralization, and calcification; 13 analyzed natural and synthetic hydroxyapatite, 50 investigated restorative dentistry and dental medicaments; 22 reported on archeological and anthropological findings, and 12 research studies were conducted in the field of forensics. Despite numerous studies being conducted on the value of vibrational spectroscopy in the characterization of dental tissues, the formulation of geographic profiles through spectroscopic analysis of chemical elements present in teeth has not been attempted hitherto. In particular, information on possible correlations between the chemical dental 'fingerprints' of people residing in the same geographic areas has not been investigated.